2015
DOI: 10.1183/13993003.00780-2015
|View full text |Cite|
|
Sign up to set email alerts
|

The burden of severe asthma in childhood and adolescence: results from the paediatric U-BIOPRED cohorts

Abstract: @ERSpublicationsChildren with severe preschool wheeze or severe asthma are usually atopic and have impaired quality of life http://ow.ly/RrrGE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
148
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(161 citation statements)
references
References 32 publications
6
148
0
7
Order By: Relevance
“…Our results are very similar to those found in the SA group of the recent European U-BIOPRED study [38], where 70% had an ACT score <19. More than half of the children in the UcSA group had an ACT score <14 owing to poorly controlled asthma and a high risk of serious exacerbations [28].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results are very similar to those found in the SA group of the recent European U-BIOPRED study [38], where 70% had an ACT score <19. More than half of the children in the UcSA group had an ACT score <14 owing to poorly controlled asthma and a high risk of serious exacerbations [28].…”
Section: Discussionsupporting
confidence: 81%
“…More than half of the children in the UcSA group had an ACT score <14 owing to poorly controlled asthma and a high risk of serious exacerbations [28]. The mean PAQLQ score was 4.3, which was slightly lower than the SA group of the European study (mean 4.7 for school-aged group) [38] and the TENOR study (5.4 in children) [30], suggesting poor quality of life among the patients in our study. Subjective measures of asthma control and quality of life are useful for identifying children with problematic asthma [40].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The EU-funded Unbiased Biomarkers for the Prediction of Respiratory Disease Outcomes (U-BIOPRED) project has just published details of their paediatric and adult severe asthma cohorts 31,32 . This cross-sectional assessment of adults with severe asthma, mild/ moderate asthma, and healthy controls from 11 European countries showed that patients with severe asthma had more symptoms and exacerbations (2.5 exacerbations versus 0.4 in the preceding 12 months) compared to patients with mild/moderate disease, with worse quality of life and higher levels of anxiety and depression.…”
Section: Phenotyping Based On Clustering Of Clinical-physiological Datamentioning
confidence: 99%
“…A major molecular mechanism of asthma is considered to be driven by type 2 T-helper cells (Th2) and eosinophilic airway inflammation in both atopic and non-atopic asthma [1]. Over recent years, however, extensive research has revealed that Th2-low subtypes are also common, particularly in severe asthma [2][3][4]. These non-Th2 asthma endotype patients may not respond adequately to usual treatment, including glucocorticosteroids and novel targeted biologics such as anti-immunoglobulin E (IgE) and anti-interleukin 5 (IL-5), and there is an urgent need for further research and therapeutic options in this group of asthmatics [5].…”
mentioning
confidence: 99%